Place Naming, Identities and Geography Critical Perspectives in a Globalizing and Standardizing World - O'Reilly, Gerry (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book presents research on geographical naming on land and sea from a wide range of standpoints on: theory and concepts, case studies and education. Space and place naming or toponymy has a long tradition in the sciences and a renewed critical interest in geography and allied disciplines including the humanities. Place: location and cartographical aspects, etymology and geo-histories so salient in past studies, are now being enhanced from a range of radical perspectives, especially in a globalizing, standardizing world with Googlization and the consequent 'normalization' of place names, perceptions and images worldwide including those for marketing purposes. Nonetheless, there are conflicting and contesting voices. The interdisciplinary research is enhanced with authors from regional, national and international toponymy-related institutions and organizations including the UNGEGN, IGU, ICA and so forth.
Introduction: Approaching place naming narratives -- Part I: Challenging conceptual and theoretical approaches to place naming -- Assessing the validity of critical toponymy perspectives for understanding human perception of places: An analytical framework -- Legacies and place naming: Perspectives from Korea and Japan -- Place naming and neotoponymy: French experiences through the lens of a Theoretical Framework -- Geographical Names in Argentina: Present and Challenges -- Toponymy, Scale and the Change of Scale. A Geographical and Linguistic Challenge -- The mystery of hydronomy in the land of Israel -- United Nations capacity building in toponymy -- Part II: Approaches to implementing standardization of place names -- Standardization of geographical names on land and sea in Slovenia -- The New Zealand geographic board and the contested nature of place names in New Zealand -- Theorising multiple place names in Southern Africa -- Conflicts and challenges in the standardisation of geographical names in Spain -- Language policies in the field of toponymy: Perspectives on Spain -- Urban toponymy in Turkey -- Cultural crossroads in toponymy: Case study of Bosnia and Herzegovina -- Part III: Geo-histories, legacies, and toponymy transitions -- Giving identity to space through (re)naming: Practice of village renaming in the period of the republic of Turkey -- Geo-history of the toponymy of Mohács Plain, SW Hungary -- Recreating the future: Modern residential neighbourhood and existing toponyms in Sarajevo -- Street-naming in Malta as a geo-cultural and political exercise as seen from local sources -- Toponymic study of the map of New Lusitania: A Portuguese cartographic monument from the 18th century -- Names and naming of collective farms in (the) Soviet Estonia -- Part IV: Toponymy: Narratives, languages, culture, and education -- Reading Ireland's colonial and postcolonial toponymic landscapes -- Translating topographies: Brian Friel's approach to language, landscape, and toponymy in Ireland -- The overlaid past: The politics of space and memory in Gibraltar's 'Doubling' street naming principle -- From historical to new place names. The case of Italy -- Geographical names represent a memory of places: Case study in Bandung Basin, West Java, Indonesia -- The vital question of placenames and naming of places in geographical education: Concepts, activities, and questions for reflection -- Part V: The relationship between geographical naming and cultural politics -- The nexus between geographical naming, place, and the politics of power.
Keywords: Human geography; History; Political science; Sociology; Anthropology; Philology; Human Geography; History; Politics and International Studies; Sociology; Anthropology; Philology